Aptitude of Graphene Oxide–Silver in Advance Polymer Nanocomposite: A Review. Issue 4 (4th March 2018) - Kausar, Ayesha; Ilyas, Hafsa; Siddiq, Muhammad
ABSTRACT: This is a state-of-the art overview on polymer/graphene oxide–silver nanoparticle nanocomposite. Different polymer/graphene oxide–silver nanoparticle categories have been elucidated using polyethersulfone, polyimides, polyindole, poly(vinylidene fluoride), polyaniline, polyvinyl pyrrolidone, and poly(3, 4-ethylenedioxythiophene). In situ reduction of silver salt and particle decoration on graphene oxide surface were effective to develop interaction between nanoparticles. Essential features of polymer/graphene oxide–silver nanoparticle revealed several advance technical applications. Conducting polymer/graphene oxide–silver nanoparticle is promising material for sensor, supercapacitor, and electrodes. Polymer/graphene oxide–silver nanoparticle possesses relevance in cancer treatment, gene transfection, cellular probing, imaging, antibacterial action, etc. Polyimide/graphene oxide–silver nanoparticle can also effectively prevent membrane bifouling. Catalytic activity of composites was also detected toward oxygen reduction in energy devices. GRAPHICAL ABSTRACT: